2021
DOI: 10.1007/s00784-021-03778-y
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of how alveolar ridge preservation affects the need of alveolar ridge augmentation at posterior tooth implant sites

Abstract: Objectives The aim of this study was to assess whether alveolar ridge preservation (ARP) can reduce the need of ridge augmentation at posterior tooth sites. Material and methods This study enrolled patients who received dental implants at posterior tooth sites during 2013–2019. Demographic data and dental treatment histories were collected. Based on healing patterns after tooth extraction, patients were divided into ARP and spontaneous healing (SH) groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…These study results suggested that ridge preservation reduced the invasiveness and complexity of future implant treatment in the maxillary molar extraction sockets with severe periodontitis. The efficacy of socket grafting in attenuating the necessity of advanced regenerative procedures at implant placement herein is consistent with previous studies [22,35,36]. Cha et al [22] reported that simple implant placement was performed in 42.9% of ridge preservation cases, whereas in all the subjects in the natural healing group, an additional augmentation procedure was needed (100% of the cases).…”
Section: Discussionsupporting
confidence: 89%
“…These study results suggested that ridge preservation reduced the invasiveness and complexity of future implant treatment in the maxillary molar extraction sockets with severe periodontitis. The efficacy of socket grafting in attenuating the necessity of advanced regenerative procedures at implant placement herein is consistent with previous studies [22,35,36]. Cha et al [22] reported that simple implant placement was performed in 42.9% of ridge preservation cases, whereas in all the subjects in the natural healing group, an additional augmentation procedure was needed (100% of the cases).…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, the present review showed that ARP had similar effects in periodontally compromised extraction sockets, albeit with a modest outcome in terms of changes in ridge width. With respect to the need for additional augmentation at the time of implant placement, our findings were in accordance with other reviews and retrospective cohort studies (Hu et al, 2021; Jung et al, 2018), where ARP has been shown to significantly minimize the need for additional bone grafting at the time of implant placement. However, a recently published Cochrane review (Atieh et al, 2021) failed to show any significant differences between ARP and extraction alone in terms of the need for additional augmentation, but the majority of the studies in the Cochrane review included four‐wall extraction sockets.…”
Section: Discussionsupporting
confidence: 92%
“…ARP is effective in maintaining alveolar ridge dimensions, which normally decrease after dental extraction, 16,35 thereby decreasing the potential for further bone grafting to be required during implantation. 36,37 Even at sites compromised by periodontitis, ARP reduces ridge resorption more than does natural healing after dental extraction. 38,39 Studies have indicated that FDBAs prevent ridge dimensional changes and serve as scaffolding for bone formation during the placement of implants.…”
Section: Discussionmentioning
confidence: 99%